PREDIKSI PENJURUSAN IPA, IPS DAN BAHASA DENGAN MENGGUNAKAN MACHINE LEARNING - Edy Widodo (Jurnal Pelita Teknologi, 2020)
ABSTRACT Data Mining is an artificial intelligence (Artificial Intelegent) that is very useful and useful for research scientists who include machine learning, statistics and databases. Thus data mining is a research method with the aim of uncovering hidden patterns. It can also be interpreted that data mining is a very useful and useful research pattern for turning data into information. With this application, it will be easier for teachers, parents, guardians of students and students to be more practical and accurate in determining the direction of Natural Sciences, Social Sciences and Languages. Which will be the weight of the calculation of the majors determination are the SMP (National Examination) UN scores, TKD scores (Basic Ability Tests) in high school, IQ scores, students 'interest values ​​and parents' desire values ​​(being another alternative). Thus the results of these predictions will result in the appropriate and accurate major with the ability of students and girls related. Keywords: Naive Bayes, DecisionTtree, Support Vector Machine and Machine Learning